2015
DOI: 10.1111/maec.12260
|View full text |Cite
|
Sign up to set email alerts
|

How are microbial and detrital sources partitioned among and within gastropods species at East Pacific Rise hydrothermal vents?

Abstract: For the last few decades, trophic ecology has usually been investigated by using stable isotopes. However, the isotopic signatures of potential food sources in hydrothermal vent ecosystems are often unknown and so their relative contribution to the consumers' diet, as well as resource partitioning, are then difficult to estimate. Here, we used a recent Bayesian mixing model (stable isotope analysis in R, SIAR) based on d C and d 15N to estimate the contribution of multiple food sources to the diet of eight ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
(215 reference statements)
0
3
0
Order By: Relevance
“…Shifts in trophic resource use and expansion of trophic niche widths in fishes inhabiting freshwater sulfide springs have been linked to changes in resource availability and competitive release (Tobler et al 2015). In contrast, competition and resulting niche partitioning among species have been documented in other H 2 S-rich environments (Gaudron et al 2015, Levesque et al 2003. Accordingly, evidence that competitive release provides an advantage for H 2 S-tolerant species is mixed.…”
Section: Hydrogen Sulfide-rich Environments and Ecological Opportunitymentioning
confidence: 99%
“…Shifts in trophic resource use and expansion of trophic niche widths in fishes inhabiting freshwater sulfide springs have been linked to changes in resource availability and competitive release (Tobler et al 2015). In contrast, competition and resulting niche partitioning among species have been documented in other H 2 S-rich environments (Gaudron et al 2015, Levesque et al 2003. Accordingly, evidence that competitive release provides an advantage for H 2 S-tolerant species is mixed.…”
Section: Hydrogen Sulfide-rich Environments and Ecological Opportunitymentioning
confidence: 99%
“…This species is endemic to the East Pacific Rise vents and is often found in abundance on Riftia tubes (Wareń and Bouchet, 1989). Campylobacteria have been reported extracellularly on gill tissue of this species in association with lysosomes, indicating possible endocytotic digestion (Zbinden et al, 2015).…”
Section: Chemosymbiosis In Gastropodamentioning
confidence: 92%
“…The abundance and large distribution of this genus may be related, among other factors, to its feeding plasticity and high mobility. In fact, these limpets exhibit various feeding strategies including grazing with their radula, active suspension feeding and even symbiotic relationships (Bates, 2007;Gaudron et al, 2015) and they are able to adjust their position in response to environmental changes (Bates et al, 2005). Their continuous reproduction and planktonic dispersal strategy also make them effective early colonizers (Kelly and Metaxas, 2007;Matabos et al, 2008;Tyler et al, 2008;Bayer et al, 2011;Nakamura et al, 2014) as observed by their rapid colonization after an eruption at the EPR (Bayer et al, 2011).…”
Section: Comparison With Other Vent Gastropod Assemblagesmentioning
confidence: 99%